Risk factors for postpartum depression in women living with HIV attending prevention of mother-to-child transmission clinic at Kenyatta National Hospital, Nairobi. Issue 7 (2nd July 2016) - Yator, Obadia; Mathai, Muthoni; Vander Stoep, Ann; Rao, Deepa; Kumar, Manasi
ABSTRACT: Mothers with HIV are at high risk of a range of psychosocial issues that may impact HIV disease progression for themselves and their children. Stigma has also become a substantial barrier to accessing HIV/AIDS care and prevention services. The study objective was to determine the prevalence and severity of postpartum depression (PPD) among women living with HIV and to further understand the impact of stigma and other psychosocial factors in 123 women living with HIV attending prevention of mother-to-child transmission (PMTCT) clinic at Kenyatta National Hospital located in Nairobi, Kenya. We used the Edinburgh Postnatal Depression Scale and HIV/AIDS Stigma Instrument – PLWHA (HASI – P). Forty-eight percent ( N  = 59) of women screened positive for elevated depressive symptoms. Eleven (9%) of the participants reported high levels of stigma. Multivariate analyses showed that lower education (OR = 0.14, 95% CI [0.04–0.46], p  = .001) and lack of family support (OR = 2.49, 95% CI [1.14–5.42], p  = .02) were associated with the presence of elevated depressive symptoms. The presence of stigma implied more than ninefold risk of development of PPD (OR = 9.44, 95% CI [1.132–78.79], p  = .04). Stigma was positively correlated with an increase in PPD. PMTCT is an ideal context to reach out to women to address mental health problems especially depression screening and offering psychosocial treatments bolstering quality of life of the mother–baby dyad.